The Canadian yearbook of international law : Annuaire canadien de droit international. - Bourne, Charles B. (Canadian Yearbook of International Law Series., 1995)
The Canadian Yearbook of International Law is issued annually under the auspices of the Canadian Branch of the International Law Association (Canadian Society of International Law) and the Canadian Council on International Law. The Yearbook contains articles of lasting significance in the field of international legal studies, a notes and comments section, a digest of international economic law, a section on current Canadian practice in international law, a digest of important Canadian cases in the fields of public international law, private international law, and conflict of laws, a list of.